Social Support and Educational Resilience: A Systematic Review of Students Facing Academic Challenges - Geizy Azhari Putri (Yayasan Vifada Cendikia Indonesia, 2024)
This study aims to provide a comprehensive synthesis of existing research on the role of social support in fostering educational resilience among students facing academic challenges. By examining different forms of social support—emotional, instrumental, informational, and evaluative—, this study seeks to understand how these factors contribute to student's academic persistence, self-efficacy, and overall well-being. Furthermore, it explores how cultural and socioeconomic contexts influence the accessibility and effectiveness of social support in various educational settings. This study employs a Systematic Literature Review (SLR) approach, analyzing relevant peer-reviewed articles published after 2018 by Elsevier, Wiley, Springer, and Emerald. The study systematically reviews the literature to identify key mechanisms through which social support enhances educational resilience, highlighting variations across educational environments and socioeconomic backgrounds. The findings indicate that social support is crucial in mitigating academic stress, enhancing self-regulated learning, and improving students' psychological well-being. Emotional and instrumental support from family and teachers significantly influences students' motivation and academic engagement. Additionally, cultural and economic factors shape how students perceive and benefit from social support. The discussion explores how integrating social support mechanisms into education policies and school programs can strengthen students' resilience. This study provides practical implications for educators, institutions, and policymakers, emphasizing the need for academic mentoring programs, counseling services, and inclusive education policies to ensure equitable access to social support. Future research should explore longitudinal studies and the impact of digital platforms in providing academic and psychological support to students.